2021
DOI: 10.1002/adom.202100510
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Photoinduced Heat Generation by Plasmonic HfN Nanoparticles

Abstract: carrier generation. [1,2] This has led to sig nificant interest in plasmonic nanostruc tures for photocatalysis, either through local heat generation or as a photo sensitizer. [3,4] Materials in the family of plasmonic transition metal nitrides (e.g., TiN, HfN, NbN, WN) feature high ther momechanical robustness and recently have been proposed for applications requiring extreme operating conditions, such as photothermal catalysis or solar thermophoto voltaics. [5] These materials have high melting points and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 82 publications
(152 reference statements)
4
23
0
Order By: Relevance
“…In general, replacing Ag and Au with cheap materials, exhibiting plasmonic resonances matching with the solar spectrum is one of the main open challenges of the whole plasmonic community. [ 23 ] Recently, several candidates for have emerged, such as nitrides (TiN [ 24 ] and HfN [ 25 ] ), SnS 2 [ 26 ] /SnSe 2 , [ 27 ] Xenes (phosphorene, [ 28 ] arsenene, [ 29 ] stanene [ 30 ] ), titanium carbides (namely, MXenes [ 31 ] ), metal oxides, [ 32 ] etc. However, most of them have poor photothermal efficacy [ 10e ] and high chemical instability with spontaneous oxidation already at room temperature, as in the case of Xenes [ 33 ] or tin dichalcogenides.…”
Section: Figurementioning
confidence: 99%
“…In general, replacing Ag and Au with cheap materials, exhibiting plasmonic resonances matching with the solar spectrum is one of the main open challenges of the whole plasmonic community. [ 23 ] Recently, several candidates for have emerged, such as nitrides (TiN [ 24 ] and HfN [ 25 ] ), SnS 2 [ 26 ] /SnSe 2 , [ 27 ] Xenes (phosphorene, [ 28 ] arsenene, [ 29 ] stanene [ 30 ] ), titanium carbides (namely, MXenes [ 31 ] ), metal oxides, [ 32 ] etc. However, most of them have poor photothermal efficacy [ 10e ] and high chemical instability with spontaneous oxidation already at room temperature, as in the case of Xenes [ 33 ] or tin dichalcogenides.…”
Section: Figurementioning
confidence: 99%
“…90 Transient absorption measurements and simulations performed on HfN NPs showed conversion of absorbed photons to heat in less than 100 fs (Figure 3D), whereas it takes a few picoseconds for this process to occur in Au. 91 The calculated electron−phonon coupling constant for HfN (1.4 × 10 18 W/m 3 K) was 50 times stronger than for Au (2.8 × 10 16 W/m 3 K) and also slightly better than that for TiN ((0.8−1.0) × 10 18 W/m 3 K) and ZrN (1.0 × 10 18 W/m 3 K). The high temperature stability accompanied by fast thermalization observed in nitrides make them attractive candidates for thermoplasmonic applications.…”
Section: ■ Fabricationmentioning
confidence: 87%
“…Recently, transition metal nitride (TMN) has received attention as an alternative plasmonic material with significant potential in the visible to near-infrared ranges of an excitation light [8], comparable to that of traditional noble metals. TMNs (e.g., titanium nitride (TiN), zirconium nitride (ZrN), and hafnium nitride (HfN)) are particularly interesting due to their high melting point, strong mechanical properties, intrinsic chemical stability in harsh environments, and localized plasmon resonances that are extremely comparable to gold [9][10][11][12]. Recent research has demonstrated that HfN exhibits exceptional quality factors for surface plasmon polaritons (SPPs) and LSPR [10,13], which are the real and imaginary components of the dielectric function.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive study on HfN thin films is aimed at controlling the stoichiometry, which is critical in determining the optical properties [11]. To form the films, physical vapor deposition (PVD) techniques, such as magnetron sputtering or pulsed laser deposition, are generally used.…”
Section: Introductionmentioning
confidence: 99%